Mitochondrial pearling is controlled by the inner membrane and mediates segregation of the luminal content and membrane scission - Wasi Iqbal; Ben Zucker; Xiaoying Liu; Ruiru Wang; Hongfei Zhu; Sijie Chen; Renjie Zhou; Xingguo Liu; Michael M. Kozlov; Liting Duan (Proceedings of the National Academy of Sciences, 2026)
Membrane pearling, the transformation of a smooth tubule into a chain of bead-like swellings connected by narrow membrane tethers, is a widely observed shape change. While it has been well studied for synthetic lipid and unilamellar intracellular membranes, the mechanism underlying the pearling of the peculiar double-membrane architecture of tubular mitochondria remained elusive. Here, we addressed the role of the strongly convoluted inner mitochondrial membrane (IMM) in pearling driven by stretching. Using a light-gated, mitochondria-specific mechanostimulator to apply stretching forces to mitochondria in live cells, we demonstrated that stretching triggers pearling of whole tubular mitochondria. Moreover, we found that pearling requires the presence of the IMM, as unilamellar tubules derived solely from the mitochondrial outer membrane elongate uniformly under stretching and never undergo pearling. To understand the physical mechanism by which IMM controls pearling, we developed a theoretical model that considers the lumen, effectively spanned and volumetrically stiffened by cristae, as an elastic continuum. Our computations show that pearling requires the luminal volume to be sufficiently resistant to change, with its effective bulk rigidity modulus exceeding a critical value. Our experimental observations further revealed the functionally important consequences of stretching-induced pearling. mtDNA nucleoids partitioned into the bulges of pearled configurations, suggesting a role for pearling in the reorganization of luminal components. In addition, the membrane fission GTPase DRP1 accumulated at the constrictions of pearled shapes, leading to membrane scission and mitochondrial fragmentation. Our work uncovers the unique biophysical mechanism of mitochondrial pearling and its functional significance for organelle dynamics.